Preparation method and application of coal pitch-based porous carbon
Through the high-temperature thermal shock treatment and the mixing of activator, the problem of difficult regulation of the specific surface area and pore size distribution of coal asphalt-based porous carbon is solved, and an efficient and low-cost preparation process is achieved, and the catalytic activity and stability of the material is improved.
Patent Information
- Application Number
- CN202411813351.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-10
AI Technical Summary
In the prior art, the specific surface area and pore size distribution of coal asphalt-based porous carbon is difficult to regulate, and the preparation process is complex, low efficiency and high cost.
The coal asphalt is preoxidized and pre-carbonized by high-temperature thermal shock treatment, oxygen-containing functional groups and heteroatoms are introduced, mixed with activators such as potassium hydroxide, and then the third high-temperature thermal shock treatment is carried out to prepare coal asphalt-based porous carbon with high specific surface area and ideal porous structure.
The specific surface area and pore structure of coal asphalt porous carbon are improved, the preparation cost and environmental protection influence are reduced, and the catalytic activity and stability of fuel cell catalysts are improved.
Smart Images

Figure CN119612513A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of material preparation, and in particular relates to a preparation method of coal tar pitch-based porous carbon and application thereof. Background Art
[0002] High-stability coal liquefaction pitch is a heavy organic substance extracted from coal through the coal liquefaction process. It has the characteristics of complex chemical composition, high carbon content, good thermal stability, high viscosity, etc. It is a carbon source for preparing porous carbon, activated carbon, carbon fiber and other materials. It has important applications in the fields of fuel cells, supercapacitor electrode materials and catalyst carriers.
[0003] There are many methods for preparing porous carbon from coal liquefaction pitch, including pyrolysis, chemical activation, physical activation and template methods. Among them, the pyrolysis method heats coal tar pitch at high temperature in an inert atmosphere to decompose and form a porous structure. The process is simple and easy to achieve large-scale production, but this method is not conducive to regulating the pore structure and specific surface area of carbon materials; the chemical activation method mixes coal tar pitch with a chemical activator (such as KOH, NaOH, K2CO3, Na2CO3, KCl, NaCl, H3PO4, etc.) and reacts at high temperature to generate porous carbon. Although this method can significantly increase the specific surface area and pore structure of carbon materials, it has high production costs and is difficult to deal with the environment; the physical activation method first carbonizes the coal tar pitch at high temperature, and then activates it at high temperature with gas (carbon dioxide, water vapor), and the porous structure formed is relatively uniform, but the activation efficiency of this method is low and the energy required is high; the template method mixes coal tar pitch with hard templates such as silica and magnesium oxide or polymer soft templates, and then through carbonization and pickling processes, the pore size and pore structure can be accurately controlled, but the process is complicated and may cause environmental pollution. Summary of the invention
[0004] The present application provides a method for preparing coal tar pitch-based porous carbon and its application, aiming to solve the problems in the prior art that the specific surface area and pore size distribution of coal tar pitch-based porous carbon are difficult to control, and the preparation process is complex, inefficient and costly.
[0005] In a first aspect of the present application, a method for preparing coal tar pitch-based porous carbon is provided, comprising the following steps:
[0006] (1) subjecting the coal tar pitch to a first high-temperature thermal shock treatment in an air atmosphere to obtain a pre-oxidized asphalt;
[0007] (2) subjecting the pre-oxidized asphalt to a second high-temperature thermal shock treatment in an inert atmosphere to obtain a pre-carbonized asphalt;
[0008] (3) The pre-carbonized asphalt and activator potassium hydroxide are mixed to obtain a mixed powder, and the mixed powder is subjected to a third high-temperature thermal shock treatment to obtain coal tar-based porous carbon.
[0009] The preparation method described in the present application utilizes high-temperature thermal shock to pre-oxidize coal tar pitch, introduce oxygen-containing functional groups, increase the content of heteroatoms, and further promote the decomposition of polycyclic aromatic hydrocarbons into small molecules, so as to improve the activation of subsequent carbonized asphalt and increase the specific surface area of coal tar pitch porous carbon.
[0010] The pre-oxidized asphalt is pre-carbonized by high-temperature thermal shock, which promotes the polymerization of coal tar precursors and improves the carbon yield of the final product. During the high-temperature thermal shock activation process, the activator melts into small droplets instantly, and the instantaneous Joule heating of high-temperature rapid quenching can effectively produce a large number of pores with uniform size distribution in the coal tar. The coal tar is more likely to interact with the activator, thereby obtaining porous carbon with an ideal porous structure and high specific surface area. This method solves the problems of long activation time, high cost, large and uneven pore structure, and relatively low specific surface area in traditional methods.
[0011] The prepared porous carbon with high specific surface area is used as a carrier of fuel cell catalyst, has high catalytic activity and stability, and shows excellent electrochemical performance.
[0012] According to some embodiments of the method for preparing coal tar pitch-based porous carbon described in the present application, in step (1), the voltage of the first high-temperature thermal shock treatment is 350-400V, and the current of the first high-temperature thermal shock treatment is 25-35A.
[0013] According to some embodiments of the method for preparing coal tar pitch-based porous carbon described in the present application, the power of the first high-temperature thermal shock treatment is 18-25 kW, and the time of the first high-temperature thermal shock treatment is 5-15 s.
[0014] According to some embodiments of the method for preparing coal tar pitch-based porous carbon described in the present application, in step (2), the voltage of the second high-temperature thermal shock treatment is 350-400V; the current of the second high-temperature thermal shock treatment is 25-35A.
[0015] According to some embodiments of the method for preparing coal tar pitch-based porous carbon described in the present application, the power of the second high-temperature thermal shock treatment is 28-32 kW, and the time of the second high-temperature thermal shock treatment is 5-20 s.
[0016] According to some embodiments of the method for preparing coal tar pitch-based porous carbon described in the present application, in step (3), the mass ratio of the pre-carbonized asphalt to the activator is (1-4):1.
[0017] According to some embodiments of the method for preparing coal tar pitch-based porous carbon described in the present application, the activator includes one or more of NaOH, K2CO3, Na2CO3, ZnCl2, KCl, NaCl and H3PO4.
[0018] According to some embodiments of the method for preparing coal tar pitch-based porous carbon described in the present application, the voltage of the third high-temperature thermal shock treatment is 350-400V; the current of the third high-temperature thermal shock treatment is 25-35A.
[0019] According to some embodiments of the method for preparing coal tar pitch-based porous carbon described in the present application, the power of the third high-temperature thermal shock treatment is 40-48 kW, and the time of the third high-temperature thermal shock treatment is 10-30 s.
[0020] According to some embodiments of the method for preparing coal tar pitch-based porous carbon described in the present application, the preparation method further includes cleaning and drying the product after the third high-temperature thermal shock treatment.
[0021] According to some embodiments of the method for preparing coal tar pitch-based porous carbon described in the present application, the cleaning is performed sequentially using hydrochloric acid and water; more preferably, the concentration of the hydrochloric acid is 1-3 mol / L.
[0022] According to some embodiments of the method for preparing coal tar pitch-based porous carbon described in the present application, the cleaning is ultrasonic cleaning, and the cleaning time is 30-60 minutes.
[0023] According to some embodiments of the method for preparing coal tar pitch-based porous carbon described in the present application, the drying temperature is 50-70° C., and the drying time is 8-12 hours.
[0024] According to some embodiments of the method for preparing the coal tar pitch-based porous carbon of the present application, the specific surface area of the coal tar pitch-based porous carbon is 1100-1200 m 2 / g.
[0025] According to some embodiments of the method for preparing the coal tar pitch-based porous carbon of the present application, the pore volume of the coal tar pitch-based porous carbon is 1.0-2.0 cm 3 / g.
[0026] According to some embodiments of the method for preparing the coal tar pitch-based porous carbon described in the present application, the pore size distribution of the coal tar pitch-based porous carbon is 4-15 nm.
[0027] According to some embodiments of the method for preparing the coal tar pitch-based porous carbon described in the present application, the thermal stability of the coal tar pitch-based porous carbon is 600-700°C.
[0028] The second aspect of the present application provides a catalyst, comprising coal tar pitch-based porous carbon obtained by the preparation method described in the first aspect of the present application, and metal nanoparticles supported on the coal tar pitch-based porous carbon.
[0029] The porous carbon obtained by the preparation method described in the present application has a high specific surface area and good stability. When used as a catalyst carrier to prepare a fuel cell catalyst, the obtained catalyst has high catalytic activity and cycle stability, and shows high electrocatalytic performance.
[0030] According to some embodiments of the catalyst described in the present application, the mass ratio of the coal tar pitch-based porous carbon to the metal nanoparticles is 5:(4-8).
[0031] According to some embodiments of the catalyst described herein, the metal nanoparticles are derived from one or more of chloroplatinic acid, chloroauric acid, chloroiridic acid and ruthenium chloride.
[0032] In a third aspect of the present application, a working electrode is provided, wherein the working electrode comprises the catalyst described in the second aspect of the present application.
[0033] According to some embodiments of the working electrode described in the present application, the catalyst loading on the working electrode is 10-200 μg / cm 2 .
[0034] The coal tar pitch-based porous carbon described in the present application can be applied to fuel cells, electrochemistry and the like. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1a The N2 adsorption-desorption isotherm of the coal tar pitch-based porous carbon prepared in Example 5;
[0036] Figure 1b is the pore size distribution curve of the coal tar pitch based porous carbon prepared in Example 5;
[0037] Figure 2 This is a transmission electron microscopy image of the coal tar pitch-based porous carbon prepared in Example 1 of the present application;
[0038] Figure 3 This is a transmission electron microscopy image of the coal tar pitch-based porous carbon prepared in Example 2 of the present application;
[0039] Figure 4 This is a transmission electron microscopy image of the coal tar pitch-based porous carbon prepared in Example 3 of the present application;
[0040] Figure 5 This is a transmission electron microscopy image of the coal tar pitch-based porous carbon prepared in Example 4 of the present application;
[0041] Figure 6This is a transmission electron microscopy image of the coal tar pitch-based porous carbon prepared in Example 5 of the present application;
[0042] Figure 7 The infrared spectra of the coal tar pitch based porous carbon prepared in Example 1 and Comparative Example 1 of the present application;
[0043] Figure 8 The Raman spectra of the coal tar pitch based porous carbon prepared in Example 1 and Comparative Example 2 of the present application;
[0044] Fig. 9 Thermogravimetric analysis curves of coal tar pitch-based porous carbon prepared in Example 1 and Comparative Example 3 of the present application;
[0045] Fig.10 The X-ray diffraction spectrum of the coal tar pitch-based porous carbon prepared in Examples 1-5 of the present application;
[0046] Fig.11 This is a SEM image of the coal tar pitch-based porous carbon prepared in Example 2 of the present application;
[0047] Fig.12 This is a SEM image of the coal tar pitch based porous carbon prepared in Comparative Example 3 of the present application;
[0048] Fig.13 The cyclic voltammetry curves of the working electrodes prepared from the coal tar pitch-based porous carbons described in Example 3 and Comparative Example 2 of the present application are shown in FIG.
[0049] Fig.14 1 and 2 are polarization curves of working electrodes prepared from the coal tar pitch-based porous carbon described in Example 3 and Comparative Example 2 of the present application, respectively. DETAILED DESCRIPTION
[0050] Embodiments of the present invention are described in detail below, and examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and intended to be used to explain the present invention, but should not be understood as limiting the present invention.
[0051] In the present invention, the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the described specific features, structures, materials or characteristics may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0052] The present invention provides a method for preparing coal tar pitch-based porous carbon, comprising the following steps:
[0053] (1) subjecting the coal tar pitch to a first high-temperature thermal shock treatment in an air atmosphere to obtain a pre-oxidized asphalt;
[0054] (2) subjecting the pre-oxidized asphalt to a second high-temperature thermal shock treatment in an inert atmosphere to obtain a pre-carbonized asphalt;
[0055] (3) The pre-carbonized asphalt and activator potassium hydroxide are mixed to obtain a mixed powder, and the mixed powder is subjected to a third high-temperature thermal shock treatment to obtain coal tar-based porous carbon.
[0056] The preparation method described in the present application utilizes high-temperature thermal shock to pre-oxidize coal tar pitch, introduce oxygen-containing functional groups, increase the content of heteroatoms, and further promote the decomposition of polycyclic aromatic hydrocarbons into small molecules, so as to improve the activation of subsequent carbonized asphalt and increase the specific surface area of coal tar pitch porous carbon.
[0057] The pre-oxidized asphalt is pre-carbonized by high-temperature thermal shock, which promotes the polymerization of coal tar precursors and improves the carbon yield of the final product. During the high-temperature thermal shock activation process, the activator melts into small droplets instantly, and the instantaneous Joule heating of high-temperature rapid quenching can effectively produce a large number of pores with uniform size distribution in the coal tar. The coal tar is more likely to interact with the activator, thereby obtaining porous carbon with an ideal porous structure and high specific surface area. This method solves the problems of long activation time, high cost, large and uneven pore structure, and relatively low specific surface area in traditional methods.
[0058] The prepared porous carbon with high specific surface area is used as a carrier of fuel cell catalyst, has high catalytic activity and stability, and shows excellent electrochemical performance.
[0059] In some embodiments of the present application, the softening point of coal tar pitch is 100-130° C., and the quinoline insoluble matter in coal tar pitch is less than 0.01%. Coal tar pitch generally needs to be crushed before pre-oxidation treatment, that is, the coal tar pitch is placed in a crusher for crushing treatment, and then the coal tar pitch is screened through a 100-mesh standard sieve.
[0060] In some embodiments of the present application, in step (1), the voltage of the first high-temperature thermal shock treatment is 350-400V; for example, 350V, 380V, 390V, 400V, etc., and the current of the first high-temperature thermal shock treatment is 25-35A; for example, 25A, 28A, 30A, 32A, 33A, 35A, etc.
[0061] The first high-temperature thermal shock treatment is performed by evenly spreading the coal tar pitch on the carbon cloth electrode, connecting the carbon cloth electrode loaded with the coal tar pitch powder to a DC source with a current pulse in an instantaneous electric heating device, and performing a pre-oxidation treatment in an air atmosphere.
[0062] In some embodiments of the present application, the power of the first high-temperature thermal shock treatment is 18-25kW, such as 18kW, 20kW, 22kW, 25kW, etc., and the time of the first high-temperature thermal shock treatment is 5-15s, such as 5s, 8s, 10s, 12s, 15s, etc. Under this thermal shock condition, the thermal shock temperature can be maintained in the range of 250-400°C, which is conducive to the decomposition of polycyclic aromatic hydrocarbons, ensures that the heteroatom content is moderate, and obtains a better pre-oxidation effect.
[0063] In some embodiments of the present application, in step (2), the voltage of the second high-temperature thermal shock treatment is 350-400V; for example, 350V, 380V, 390V, 400V, etc., and the current of the second high-temperature thermal shock treatment is 25-35A; for example, 25A, 28A, 30A, 32A, 33A, 35A, etc.
[0064] In some embodiments of the present application, the power of the second high-temperature thermal shock treatment is 28-32kW, such as 28kW, 30kW, 32kW, etc., and the time of the second high-temperature thermal shock treatment is 5-20s, such as 5s, 10s, 12s, 15s, 18s, 20s, etc. Within this power range, the thermal shock temperature can be controlled in the range of 450-650°C, which can improve the carbon yield of subsequent products and optimize the pre-carbonization effect.
[0065] The second high-temperature thermal shock method is to evenly spread the pre-oxidized coal tar powder on the carbon cloth electrode, connect the carbon cloth electrode loaded with the pre-oxidized coal tar powder to a DC source with current pulses in an instantaneous electric heating device, and protect heating in a nitrogen range to perform pre-carbonization treatment.
[0066] In some embodiments of the present application, in step (3), the mass ratio of the pre-carbonized coal tar pitch and the activator is (1-4):1; for example, 4:1, 3:1, 2:1, 1:1, etc. The pre-carbonized coal tar pitch and the activator are uniformly mixed with a mixing vibration ball mill for 1-5 minutes, and then the mixed powder is evenly spread on the carbon cloth electrode, and the carbon cloth electrode loaded with the mixed powder is connected to a DC source with a current pulse in an instantaneous electric heating device, and protected and heated in a nitrogen atmosphere.
[0067] In some embodiments of the present application, the activator includes one or more of NaOH, K2CO3, Na2CO3, ZnCl2, KCl, NaCl and H3PO4.
[0068] In some embodiments of the present application, the voltage of the third high-temperature thermal shock treatment is 350-400V; for example, 350V, 380V, 390V, 400V, etc., and the current of the third high-temperature thermal shock treatment is 25-35A, for example, 25A, 28A, 30A, 32A, 33A, 35A, etc.
[0069] In some embodiments of the present application, the power of the third high-temperature thermal shock treatment is 40-48kW, for example, 40kW, 42kW, 45kW, 46kW, 48kW, etc., and the time of the third high-temperature thermal shock treatment is 10-30s, for example, 10s, 15s, 18s, 20s, 22s, 26s, 28s, 30s, etc. Under this condition, the temperature of the thermal shock can be controlled in the range of 650-1000°C, which helps to improve the stability and specific surface area of the product and achieve the best activation effect.
[0070] In some embodiments of the present application, the preparation method further comprises cleaning and drying the product after the third high-temperature thermal shock treatment.
[0071] In some embodiments of the present application, the cleaning is performed using hydrochloric acid and water in sequence.
[0072] In some embodiments of the present application, the concentration of the hydrochloric acid is 1-3 mol / L, for example, 1 mol / L, 2 mol / L, 3 mol / L, etc.
[0073] In some embodiments of the present application, the cleaning is ultrasonic cleaning, and the cleaning time is 30-60 min, for example, 30 min, 35 min, 40 min, 45 min, 50 min, 55 min, 60 min, etc.
[0074] In some embodiments of the present application, the drying temperature is 50-70°C, for example, 50°C, 60°C, 65°C, 70°C, etc., and the drying time is 8-12h, for example, 8h, 10h, 11h, 12h, etc.
[0075] In some embodiments of the present application, the specific surface area of the coal tar-based porous carbon is 1100-1200 m 2 / g; for example, 1100m 2 / g, 1150m 2 / g, 1180m 2 / g, 1185m 2 / g, 1120m 2 / g, etc.
[0076] In some embodiments of the present application, the pore volume of the coal tar-based porous carbon is 1.0-2.0 cm 3 / g; for example 1.0cm 3 / g, 1.2cm 3 / g, 1.22cm 3 / g, 1.28cm 3 / g, 1.83cm 3 / g, 1.89cm 3 / g, 2.0cm 3 / g, etc.
[0077] In some embodiments of the present application, the pore size distribution of the coal tar-based porous carbon is 4-15 nm; for example, 4 nm, 8 nm, 9 nm, 10 nm, 12 nm, 15 nm, etc.
[0078] In some embodiments of the present application, the thermal stability of the coal tar-based porous carbon is 600-700°C; for example, 600°C, 620°C, 650°C, 680°C, 690°C, 700°C, etc.
[0079] In a second aspect of the present application, a catalyst is provided, comprising a coal tar pitch-based porous carbon obtained by the preparation method described in the first aspect of the present application, and metal nanoparticles supported on the coal tar pitch-based porous carbon. The catalyst has an electrochemical active area of 165.8 m at 25°C, in a three-electrode system, with N2 saturated with 0.1 mol / L HClO4 as the electrolyte, in a scanning range of -0.1 to 1.2 V, and a speed rate of 50 mV / s. 2 / g, current density at 0.9V 4.41mA / cm 2 .
[0080] In some embodiments of the present application, 500 mg of the coal tar pitch-based porous carbon (the coal tar pitch-based porous carbon described in the first aspect of the present application) is weighed with an electronic balance, dispersed in an ethanol-water solution (the volume percentage of ethanol: 1%-30%), and a certain amount (mass percentage is 20%-80%, for example, 20%, 40%, 60%, 80%) of a noble metal precursor (such as chloroplatinic acid, chloroauric acid, chloroiridic acid, ruthenium chloride, etc.) is added, and the mixture is stirred and dissolved for 30 minutes;
[0081] (2) Add an excess of reducing agent (such as HCHO, HCOONa, Na2SO3, NH2NH2, NaBH4, etc.) and add 5% to 15% of the mass of the aqueous solution of a charged surfactant (such as quaternary ammonium salt, PPh3, PVP, PVA, etc.) in the temperature range of 25-55°C; during the catalyst preparation process, the addition of a surfactant can effectively disperse the precious metal nanoparticles and increase the active specific surface area of the catalyst.
[0082] (3) Under the assistance of ultrasonic waves of certain power (50 W, 100 W, 200 W), the reduction reaction and the dispersion of raw materials were promoted to prepare a porous carbon@metal element catalyst slurry, which was then washed by centrifugation with deionized water for multiple times and vacuum dried at 60 °C for 8-12 h to obtain a catalyst.
[0083] In some embodiments of the present application, the mass ratio of the coal tar-based porous carbon to the metal compound is 5:(4-8); for example, 5:4, 5:5, 5:6, 5:7, 5:8, etc.
[0084] In some embodiments of the present application, the metal compound includes one or more of chloroplatinic acid, chloroauric acid, chloroiridic acid and ruthenium chloride.
[0085] An embodiment of the present application also provides a working electrode, which includes the catalyst described in the second aspect of the present application.
[0086] In some embodiments of the present application, the catalyst loading on the working electrode is 10-200 μg / cm 2 , for example 10 μg / cm 2 , 20μg / cm 2 , 50μg / cm 2 , 80μg / cm 2 , 100μg / cm 2 , 120μg / cm 2 , 130μg / cm 2 , 160μg / cm 2 , 180μg / cm 2 , 200μg / cm 2 wait.
[0087] The porous carbon obtained by the preparation method described in the present application has a high specific surface area and good stability. When used as a catalyst carrier to prepare a fuel cell catalyst, the obtained catalyst has high catalytic activity and cycle stability, and shows high electrocatalytic performance.
[0088] In some embodiments of the present application, 5 mg of the catalyst described in the second aspect of the present application is accurately weighed, 5-20 μl of 5% Nafion solution, ultrapure water, and isopropanol are added to the catalyst in sequence, and then ultrasonicated with an ultrasonic power greater than 200 W for 30 minutes to fully mix the slurry, and the water bath temperature is kept below 20° C. during the ultrasonication process;
[0089] The catalyst loading on the electrode surface ranges from 10 to 200 μg / cm 2 , take an appropriate amount of the dispersed slurry and evenly apply it to the smooth and clean surface of the disk electrode twice, and let it dry completely naturally as the working electrode.
[0090] The technical solution of the present application is described in detail below in conjunction with specific embodiments and drawings.
[0091] Example 1
[0092] A method for preparing coal tar pitch-based porous carbon comprises the following steps:
[0093] (1) Weigh 100 g of refined asphalt after coal liquefaction (softening point 130° C., quinoline insoluble matter <0.01%, obtained from China Shenhua Coal to Liquid Chemical Co., Ltd.), crush it with a crusher for 10 min; screen the coal tar powder with a 100-mesh standard sieve, weigh 10 g of the screened asphalt powder, and further grind it with an agate mortar; spread the ground coal tar powder evenly on a carbon cloth electrode, connect the carbon cloth loaded with coal tar powder to a DC source with a current pulse in an instantaneous electric heating device, adjust the voltage so that the power of the first high-temperature thermal shock treatment is 18 kW, heat it for 10 s at this power and in an air atmosphere to obtain pre-oxidized asphalt;
[0094] (2) Pre-oxidized coal tar pitch powder is evenly spread on a carbon cloth electrode, and the carbon cloth loaded with coal tar pitch powder is connected to a DC source with a current pulse in an instantaneous electric heating device, and the voltage is adjusted so that the power of the second high-temperature thermal shock treatment is 28 kW. The carbon cloth is heated for 10 seconds under this power and a nitrogen atmosphere to obtain a pre-carbonized asphalt;
[0095] (3) Pre-carbonized coal tar pitch and potassium hydroxide powder were uniformly mixed in a mass ratio of 2:1 using a mixed vibration ball mill for 3 minutes; the mixed powder was evenly spread on a carbon cloth electrode, and the carbon cloth loaded with the mixed powder was connected to a DC source with a current pulse in an instantaneous electric heating device, and the voltage was adjusted so that the power of the third high-temperature thermal shock treatment was 40 kW, and heated for 20 seconds under this power and nitrogen atmosphere; then the material obtained by the third high-temperature thermal shock treatment was ultrasonically cleaned with 2 mol / L HCl and deionized water in turn, and the cleaned material was vacuum dried at 60°C for 12 hours to obtain coal tar-based porous carbon.
[0096] Example 2
[0097] The only difference between the preparation method of coal tar pitch-based porous carbon described in Example 2 and that of Example 1 is that the time of the first high-temperature thermal shock treatment in the preparation method of coal tar pitch-based porous carbon described in Example 2 is 15 seconds (the carbon cloth loaded with coal tar pitch powder is connected to a DC source with current pulses in an instantaneous electric heating device for 15 seconds).
[0098] Example 3
[0099] The only difference between the preparation method of coal tar pitch-based porous carbon described in Example 3 and that in Example 1 is that the time of the second high-temperature thermal shock treatment in the preparation method of coal tar pitch-based porous carbon described in Example 3 is 20 seconds (the carbon cloth loaded with pre-oxidized coal tar pitch powder is connected to a DC source with current pulses in an instantaneous electric heating device for 20 seconds).
[0100] Example 4
[0101] The only difference between the preparation method of coal tar pitch-based porous carbon described in Example 4 and that of Example 1 is that the time of the third high-temperature thermal shock treatment in the preparation method of coal tar pitch-based porous carbon described in Example 4 is 10 seconds (the carbon cloth loaded with mixed powder is connected to a DC source with current pulses in an instantaneous electric heating device for 10 seconds).
[0102] Example 5
[0103] The only difference between the method for preparing coal tar pitch-based porous carbon described in Example 5 and that in Example 1 is that the power of the third high-temperature thermal shock treatment in the method for preparing coal tar pitch-based porous carbon described in Example 5 is 50 KW.
[0104] Comparative Example 1
[0105] The only difference between the preparation method of the coal tar pitch-based porous carbon described in Comparative Example 1 and Example 1 is that the preparation method of the coal tar pitch-based porous carbon described in Comparative Example 1 does not pre-oxidize the coal tar pitch, but directly pre-carbonizes the coal tar pitch in an inert atmosphere.
[0106] Comparative Example 2
[0107] The preparation method of the coal tar pitch-based porous carbon described in Comparative Example 2 is different from that in Example 1 only in that the preparation method of the coal tar pitch-based porous carbon described in Comparative Example 2 does not perform pre-carbonization treatment of the coal tar pitch, that is, pre-oxidized coal tar pitch and an activator are mixed to obtain a mixed powder, and the mixed powder is subjected to a third high-temperature thermal shock treatment to obtain coal tar pitch-based porous carbon.
[0108] Comparative Example 3
[0109] The only difference between the preparation method of the coal tar pitch-based porous carbon described in Comparative Example 3 and Example 1 is that the preparation method of the coal tar pitch-based porous carbon described in Comparative Example 3 does not pre-oxidize, carbonize, and activate the coal tar pitch through a high-temperature thermal shock process.
[0110] The specific operation is as follows: grind and mix coal tar and KOH in a mass ratio of 2:1, place the mixed powder in a high-temperature tubular furnace for carbonization treatment in a nitrogen atmosphere with a nitrogen flow rate of 50 mL / min, a carbonization treatment temperature of 1000°C, a heating rate of 10°C / min, and a carbonization time of 3 h.
[0111] 1. The physical properties of the coal tar pitch-based porous carbon obtained by the preparation methods described in Examples 1-5 and Comparative Examples 1-3 of the present application are studied. The results are shown in Table 1:
[0112] The N2 adsorption-desorption isotherm curves and pore size distribution of the coal tar pitch-based porous carbons described in Example 5 and Comparative Example 3 were measured by BET adsorption method. Figure 1a and Figure 1b shown.
[0113] Table 1
[0114]
[0115] Note: The specific surface area, pore volume and pore size distribution described in this application are determined by BET adsorption method.
[0116] The stability described in the present application is obtained by thermogravimetric testing. An appropriate amount of sample is weighed and placed in a test crucible of a thermogravimetric analyzer with nitrogen as the working gas. The sample is heated from room temperature to an end point temperature of 800°C at a heating rate of 10°C / min, and the sample temperature-mass curve is recorded.
[0117] The carbon yield described in the present application is the mass ratio before and after high-temperature thermal shock pre-oxidation, carbonization and activation treatment of coal tar pitch.
[0118] From Table 1, Figure 1a and Figure 1b It can be seen that the heating power and time during high-temperature thermal shock treatment have an impact on the specific surface area, pore volume, pore size distribution and stability of coal tar-based porous carbon.
[0119] From the comparison of the sample data of Example 1 and Comparative Example 1, it can be seen that the specific surface area and pore volume of the coal tar-based porous carbon can be significantly improved and the pore size distribution can be precisely controlled through high-temperature thermal shock pre-oxidation treatment, because the pre-oxidation treatment can effectively decompose polycyclic aromatic hydrocarbons and introduce heteroatoms and oxygen-containing functional groups.
[0120] From the comparison of the sample data of Example 1 and Comparative Example 2, it can be seen that the thermal stability and carbon yield of the coal base can be significantly improved through high-temperature thermal shock pre-carbonization treatment, and a product with better property parameters can be obtained.
[0121] From the comparison of the sample data of Example 1 and Comparative Example 3, it can be seen that compared with the traditional carbon activation method, the product obtained by high-temperature thermal shock has obvious advantages, such as easy operation, short process and high product performance.
[0122] 2. The high-magnification transmission electron microscopy images of the coal tar pitch-based porous carbon prepared in Examples 1-5 of the present application are as follows: Figure 2-6 shown.
[0123] from Figure 2-6It can be seen that the coal tar-based porous carbon has an obvious porous structure, but with different process parameters, the specific morphology and structure of the porous carbon sample are different. The experimental results show that Example 1 has the best property parameters, because the high-temperature thermal shock pre-oxidation and carbonization treatment time of Example 1 is moderate, which not only realizes the introduction of heteroatoms, but also improves the stability of the sample, achieving the best pretreatment effect, and the sample obtains the best specific surface area and pore volume, and the pore size distribution is precisely controlled.
[0124] 3. The infrared spectra of the coal tar pitch based porous carbon prepared in Example 1 and Comparative Example 1 of the present application are as follows: Figure 7 shown.
[0125] from Figure 7 It can be seen that the coal tar pitch-based porous carbon obtained by the preparation method described in the present application contains atomic functional groups such as C, S, N, and O. The sample of Example 1 after pre-oxidation treatment has a carbon content of 800-900 cm -1 The wavelength range has obvious CO functional group characteristic peaks, while the sample in comparative example 1 does not have obvious CO functional group characteristic peaks. Therefore, the pre-oxidation treatment has the effect of decomposing polycyclic aromatic hydrocarbons and introducing heteroatoms and oxygen-containing functional groups.
[0126] 4. The Raman spectra of the coal tar pitch based porous carbon prepared in Example 1 and Comparative Example 2 of the present application are as follows: Figure 8 shown.
[0127] from Figure 8 It can be seen that the coal tar pitch based porous carbon prepared in Example 1 of the present application has a -1 and 1590cm -1 There are two typical carbon characteristic peaks nearby, namely the D peak representing defective structure and the G peak representing ordered structure. According to the area ratio of the D peak and the G peak, I D / I G , Example 1 Sample I D / I G is 1.22, while the I of the sample in Comparative Example 1 is D / I G is 1.41, indicating that the sample in Example 1 has a higher degree of graphitization. Therefore, high-temperature thermal shock pre-carbonization treatment can significantly improve the thermal stability of coal-based materials and improve the degree of graphitization of porous carbon.
[0128] 5. The thermal gravimetric analysis curves of the coal tar pitch based porous carbon prepared in Example 1 and Comparative Example 3 of the present application are as follows: Fig. 9 shown.
[0129] from Fig. 9It can be seen that the coal tar-based porous carbon prepared in Example 1 of the present application has higher thermal stability, wherein the thermal decomposition temperature of the sample in Example 1 is 685°C, and the thermal decomposition temperature of the sample in Comparative Example 1 is 435°C.
[0130] 6. The X-ray diffraction spectra of the coal tar pitch based porous carbon prepared in Examples 1-5 of the present application are as follows: Fig.10 shown.
[0131] from Fig.10 It can be seen that the coal tar pitch-based porous carbon samples all have carbon characteristic diffraction peaks near 2θ of 23° and 44°, which correspond to the 002 diffraction peak of the aromatic sheet stacking orientation and the 100 diffraction peak of the aromatic sheet size, respectively.
[0132] 7. The SEM images of the coal tar pitch based porous carbon prepared in Example 2 and Comparative Example 3 of the present application are as follows: Fig.11 and Fig.12 shown.
[0133] from Fig.11 and Fig.12 It can be seen that the surface morphology of the coal tar pitch-based porous carbon prepared by the high-temperature thermal shock method is more uniform and regular, while the porous carbon prepared by the traditional method has a wider distribution range of pore structures and a rough and uneven surface. Therefore, the coal tar pitch-based porous carbon prepared by the high-temperature thermal shock method has a higher specific surface area.
[0134] Example 6
[0135] A method for preparing a working electrode comprises the following steps:
[0136] (1) 500 mg of the coal tar-based porous carbon prepared in Example 3 of the present application was dispersed in 20 mL of a 10% ethanol-water solution, and then 60% chloroplatinic acid was added to the aqueous solution, stirred to dissolve and mixed for 30 min; while maintaining 25° C., an excess of NaBH4 was added as a reducing agent, and then 5% quaternary ammonium salt dodecyl ammonium chloride was added as a surfactant; a reduction reaction was carried out under the assistance of an ultrasonic wave with a power of 200 W to obtain a porous carbon@Pt catalyst; the catalyst was centrifuged and washed with deionized water, and vacuum dried at 60° C. for 12 h to obtain a catalyst;
[0137] (2) Weigh 5 mg of the above catalyst, add 50 μl of 5% Nafion solution, 2 mL of ultrapure water, and 2 mL of isopropanol to the catalyst in sequence, and then use 300 W ultrasonic wave to mix the slurry evenly for 30 min. During the ultrasonic process, keep the water bath temperature below 20 ° C. According to the catalyst loading on the electrode surface of 30 μg / cm 2, take an appropriate amount of the dispersed slurry and evenly apply it to the smooth and clean surface of the disk electrode twice, place it in a moisture-proof cabinet, and dry it completely as a working electrode.
[0138] Comparative Example 4
[0139] The preparation method of the working electrode described in Comparative Example 4 is different from that in Example 6 only in that the coal tar pitch-based porous carbon prepared in Comparative Example 2 is used instead of the coal tar pitch-based porous carbon prepared in Example 3.
[0140] Performance study of the working electrode described in this application:
[0141] 1. Research method: High-purity N2 (99.99%) was introduced into a 0.1 mol / L HClO4 aqueous solution and purged for at least 30 minutes to remove dissolved oxygen in the solution. Then, in a three-electrode system, a thin film electrode was used as the working electrode (the working electrode prepared by Example 6 of the present application and the working electrode prepared by Comparative Example 4 of the present application), a saturated calomel electrode was used as the reference electrode, a Pt sheet was used as the counter electrode, and the electrolyte was a 0.1 mol / L HClO4 solution saturated with N2. Cyclic voltammetry curve test was performed at 25°C. The catalyst was first activated at a scanning speed of 100 mV / s, and the catalyst surface was cleaned until the hydrogen desorption peak area no longer increased. At 0-1.2 V (relative to the reversible hydrogen electrode, V RHE ) Under the potential scanning range, scan 5 times at a speed of 50mV / s and record the cyclic voltammetry curve at this time. The results are as follows Fig.13 shown.
[0142] from Fig.13 It can be seen that the working electrode described in Example 6 of the present application has obvious redox catalytic performance, and the catalytic performance is significantly better than that of the working electrode described in Comparative Example 4, and has a higher electrochemical active area.
[0143] 2. At 25°C, in a three-electrode system, O2-saturated 0.1 mol / L HClO4 was used as the electrolyte, the ring electrode speed was 1500 r / min, and the voltage was between 0 and 1.0 V. RHE Under the potential scanning range, the forward scanning is performed at a speed of 10 mV / s, and the polarization curve of the working electrode (the working electrode prepared by Example 6 of the present application and the working electrode prepared by Comparative Example 4 of the present application) is recorded at this time. The results are as follows: Fig.14 shown.
[0144] from Fig.14 It can be seen that the working electrode prepared in Example 6 of the present application has a voltage range of 0.1-0.6V. RHE There is a higher current density between them.
[0145] Although the above embodiments have been shown and described, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. Changes, modifications, substitutions and variations of the above embodiments by those of ordinary skill in the art are all within the scope of protection of the present invention.
Claims
1. A method for preparing coal tar pitch-based porous carbon, characterized in that: The following steps are involved: (1) subjecting the coal tar pitch to a first high-temperature thermal shock treatment in an air atmosphere to obtain a pre-oxidized asphalt; (2) subjecting the pre-oxidized asphalt to a second high-temperature thermal shock treatment in an inert atmosphere to obtain a pre-carbonized asphalt; (3) The pre-carbonized asphalt and the activator are mixed to obtain a mixed powder, and the mixed powder is subjected to a third high-temperature thermal shock treatment to obtain coal tar-based porous carbon.
2. The method for preparing coal tar pitch-based porous carbon according to claim 1, characterized in that: In step (1), the voltage of the first high-temperature thermal shock treatment is 350-400V; the current of the first high-temperature thermal shock treatment is 25-35A; And / or, the power of the first high-temperature thermal shock treatment is 18-25 kW, and the time of the first high-temperature thermal shock treatment is 5-15 s.
3. The method for preparing coal tar pitch-based porous carbon according to claim 1, characterized in that: In step (2), the voltage of the second high-temperature thermal shock treatment is 350-400V; the current of the second high-temperature thermal shock treatment is 25-35A; And / or, the power of the second high-temperature thermal shock treatment is 28-32 kW, and the time of the second high-temperature thermal shock treatment is 5-20 s.
4. The method for preparing coal tar pitch-based porous carbon according to claim 1, characterized in that: In step (3), the mass ratio of the pre-carbonized asphalt to the activator is (1-4): 1; and / or, the activator comprises one or more of NaOH, K2CO3, Na2CO3, ZnCl2, KCl, NaCl and H3PO4; And / or, the voltage of the third high temperature thermal shock treatment is 350-400V; the current of the third high temperature thermal shock treatment is 25-35A; And / or, the power of the third high-temperature thermal shock treatment is 40-48 kW, and the time of the third high-temperature thermal shock treatment is 10-30 s.
5. The method for preparing coal tar pitch-based porous carbon according to claim 1, characterized in that: The preparation method further comprises washing and drying the product after the third high-temperature thermal shock treatment; Preferably, the cleaning is performed by sequentially using hydrochloric acid and water; more preferably, the concentration of the hydrochloric acid is 1-3 mol / L; Preferably, the cleaning is ultrasonic cleaning, and the cleaning time is 30-60 minutes; Preferably, the drying temperature is 50-70° C., and the drying time is 8-12 hours.
6. The method for preparing coal tar pitch-based porous carbon according to claim 1, characterized in that: The specific surface area of the coal tar-based porous carbon is 1100-1200m 2 / g; And / or, the pore volume of the coal tar-based porous carbon is 1.0-2.0 cm 3 / g; and / or, the pore size distribution of the coal tar pitch based porous carbon is 4-15 nm; And / or, the thermal stability of the coal tar pitch based porous carbon is 600-700°C.
7. A catalyst, characterized in that The invention comprises coal tar pitch-based porous carbon obtained by the preparation method according to any one of claims 1 to 6, and metal nanoparticles supported on the coal tar pitch-based porous carbon.
8. The catalyst according to claim 7, characterized in that The mass ratio of the coal tar pitch-based porous carbon to the metal nanoparticles is 5:(4-8); And / or, the metal nanoparticles are derived from one or more of chloroplatinic acid, chloroauric acid, chloroiridic acid and ruthenium chloride.
9. A working electrode, characterized in that The working electrode comprises the catalyst according to any one of claims 7-8.
10. The working electrode according to claim 9, characterized in that The loading amount of the catalyst on the working electrode is 10-200 μg / cm 2 .
Citation Information
Patent Citations
Method and apparatus for surface treatment of carbon fibre
CN1082131A
Method for preparing foam carbon by casting non-aqueous gel
CN109704768A
Preparation method of carbon fiber reinforced carbon-based composite material honeycomb
CN110282994A
Preparation method of coal-based porous carbon
CN113307267A
Rapid graphitization method based on pulse high-temperature Joule heating
CN115924901A
Cited By
Method for preparing high-defect coal pitch-based porous carbon through in-situ oxidation-carbonization in air
CN121394187A
Porous carbon as well as preparation method and application thereof
CN121913483A